A giant floating thrombus in the ascending aorta: a case report - Yang, Peng (BMC Surg, 2020)
BACKGROUND: A floating thrombus in an ascending aorta with normal morphology is very rare, but when it does occur, it may induce a systemic embolism or fatal stroke. The pathophysiological mechanisms of aortic mural thrombi remain unclear, and there is no consensus regarding therapeutic recommendations. CASE PRESENTATION: We report a 49-year-old male who presented with chest discomfort for 5 days and was admitted to our emergency unit. A contrast-enhanced computed tomography angiography (CTA) surprisingly demonstrated a large filling defect suggestive of a thrombus in his otherwise healthy distal ascending aorta. Surgical resection of the mass and attachment site was performed. Histological examination confirmed that the mass was a thrombus, but the cause of the thrombus formation was unknown. CONCLUSIONS: floating aortic thrombi are rare, and they are prone to break off, thus carrying a potential risk for embolic events with catastrophic consequences. Surgical resection, both of the aortic thrombus and attachment site, as well as postoperative anticoagulant administration, are standard treatments.